Strategi Pembelajaran Shorof dalam Meningkatkan Kemampuan Mahasiswa Menerapkan Dhamir pada Mata Kuliah Bahasa Arab di STAI Ali bin Abi Thalib Surabaya - Muhammad Rafii Athaillah; Ridho Ahmad Rasyid Waluyo; Abdurrahman Dzaky Al Rasyid; Muhammad Abi Zaard; Angger Bimantara (Jurnal Ilmiah Literasi Indonesia, 2026)
This research is motivated by the importance of mastering the science of shorof in Arabic language learning, especially the ability of students to apply dhamir who still face various obstacles in language practice. This study aims to analyze the ability of students in applying dhamir, identify the obstacles faced, and describe the learning strategies of shorof used to improve these abilities. The study used a descriptive qualitative approach with research subjects of second semester students of the Arabic Language Education Study Program of STAI Ali bin Abi Thalib Surabaya and lecturers in charge of shorof courses. Data were collected through observation, interviews, and documentation, then analyzed descriptively through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the ability of students in applying dhamir is in the fairly good category, as indicated by the ability to distinguish types of dhamir, change the form of fi’il according to dhamir, and use it in simple sentences. Obstacles found include lack of habituation and murojaah, differences in educational background, as well as difficulties in certain forms of fi’il and the use of dhamir that are rarely used. The learning strategies implemented included hands-on practice, repeated tashrif exercises, familiarization with the use of dhamir in sentences, and intensive lecturer guidance, which were proven to help improve students' ability to apply dhamir. Thus, learning that integrates theory and practice continuously can support students' ability to use dhamir in Arabic language courses.